Mortality profile of Covid-19 patients in the municipality of Cascavel in the years 2020 and 2021 (Research, Society and Development, 2022)
Covid-19, a viral disease caused by SARS-CoV-2, reached pandemic status in March 2020. Since then, epidemiological studies have been essential to comprehend the profile of patients who develop serious complications and have higher fatality rates. Therefore, this study sought to understand the mortality profile of the disease in the municipality of Cascavel and concluded that deaths are concentrated in the male population, with emphasis on retirees with chronic comorbidities, mainly Systemic Arterial Hypertension and Diabetes Mellitus. These results were consistent with the literature developed from similar works. Furthermore, this work proposed to present justifications that explain this predominant mortality profile in Cascavel.